VI coisas tão prodigiosas quanto tantas outras tidas por impossíveis” : o maravilhoso entre o natural e o sobrenatural na América portuguesa (século XVI) - Silva, Kelvin Oliveira da (2021)
In the first century of colonization of Brazil, travel reports, Jesuit letters, treaties, relations and other writings of colonial agents, as well as iconography of various kinds, produced both in the colony and in Europe, bequeathed us abundant surprisingly beautiful and horrible impressions of the most diverse aspects of the earth. The combination of these impressions has occasioned the investigation of the wonderful – essential component of the European imaginary on the Portuguese America of the five hundred. The investigation unfolded in the broad manifestations of the wonderful, encompassing both the terrain of what we call with some inaccuracy of "supernatural" and the terrain of the "natural". In the case of the first terrain, we approach the presence of God and the devil, as well as to look at descriptions of monstrous and mythical peoples. As for the second terrain, we discuss nature itself, including views on general aspects of the nature of Brazil, as well as flora and fauna. Having drawn up a general picture of this imaginary, we were able to observe how the wonderful presented itself and what constituted it, how its presence was possible, the place it held in the colonizing process and in an imaginary about Brazil. It was also possible to observe if there were possible differences between people from different regions of Europe and from different social groups. Moreover, we notice the collaboration of the wonderful in the construction of the Other American. Throughout the research, we kept an eye on the presence of the medieval in our sources, even though we did not necessarily see it as continuity. It was the specificity of the wonderful about and in Brazil of the sixteenth century, after all, what we seek here.